Coking behavior of nickel and a rhodium based catalyst used in steam reforming for power-to-gas applications - Großmann, Katharina; Dellermann, Thomas; Dillig, Marius; Karl, Jürgen (International Journal of Hydrogen Energy, 2017)

Development and testing of a new concept for regenerative porous burner with preheated air - Großmann, Katharina; Zbogar-Rasic, Ana; Jovicic, Vojislav; Bauer, Herbert; Delgado, Antonio (Proceedings of the 9th European conference on industrial furnaces and boilers, 2011)
UnivIS-Import:2017-11-06:Pub.2011.tech.ITC.stmmec.develo

Optimization of Fuel Inlet Configuration for Porous Burners with Preheated Air - Großmann, Katharina; Zbogar-Rasic, Ana; Jovicic, Vojislav; Delgado, Antonio; Bauer, Herbert (Proceedings of the European Combustion Meeting 2011, 2011)
UnivIS-Import:2017-11-06:Pub.2011.tech.ITC.stmmec.optimi_8

Optimization of inlet mixture quality by means of third gas for regenerative porous burners with highly preheated air - Zbogar-Rasic, Ana; Großmann, Katharina; Nienhaus, Christoph; Jovicic, Vojislav; Bauer, Herbert; Delgado, Antonio (Proceedings of the 6th European Combustion Meeting (ECM 6), 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.optimi

PtG without electrolysis: Hydrogen production from renewable sources in the natural gas grid by partial reforming - Großmann, Katharina; Karl, Jürgen (REGATEC 2016: 3rd International Conference on Renewable Energy Gas Technology, 2016)

Steam methane reforming at low S/C ratios for power-to-gas applications - Großmann, Katharina; Treiber, Peter; Karl, Jürgen (International Journal of Hydrogen Energy, 2016)
Steam reforming is a well-established industrial process for the production of hydrogen from hydrocarbon fuels, in most cases from natural gas. High steam to carbon ratios are applied to gain maximum methane conversion. Since steam reforming of natural gas is a highly endothermic reaction it may also be applied as a chemical storage of renewable energy. For this power-to-hydrogen application milder conditions and shorter operating times are characteristic. However process efficiency declines with increasing S/C ratio for storage applications. Though, when lowering S/C ratios one of the major challenges lies in coke formation due to unwanted reactions. On this reason, experiments with different hydrocarbon feedstock, including methane and a synthetic natural gas mixture were conducted in a laboratory test rig to investigate the influence of very low S/C ratios in the range of 0.1e0.4 and reaction temperatures between 450 and 500 °C at atmospheric pressure. Measurements showed drastic decrease of catalyst life times when small amounts of ethane and propane were added to the hydrocarbon feedstock. Long-term tests showed that catalyst deactivation led to flattening of the temperature profile, changes in dry product gas composition and rising pressure drop over fixed bed. Increase of reaction temperature, lowering of S/C and use of higher hydrocarbons in the feed led to intense carbon lay down.
Keywords: Hydrogen; Heterogeneous catalyst; Steam reforming; Coke formation; S/C ratio; Power-to-gas